Consumer credit usage in Canada during the coronavirus pandemic. (11th February 2022) - Ho, Anson T. Y.; Morin, Lealand; Paarsch, Harry J.; Huynh, Kim P.
Abstract: The recent COVID‐19 pandemic has devastated economies worldwide. Using detailed, monthly data from a major consumer credit reporting agency in Canada, we have examined individuals' use of credit cards and home‐equity lines of credit (HELOCs). We found a dramatic leftward shift in the distribution of credit card and HELOC outstanding balances, providing evidence for a widespread reduction in credit usage. Our findings suggest that, during the COVID‐19 recession, Canadian consumers were able to meet their financial needs without increasing their debt burdens. These results complement other findings concerning a decline in consumer spending and the results of government assistance programs, and imply that the economic consequences of this pandemic are very different from those in other recessions. Résumé: Recours au crédit à la consommation au Canada au cours de la pandémie de coronavirus . La récente pandémie de COVID‐19 a ravagé les économies mondiales. Grâce aux données mensuelles détaillées d'une des agences d'évaluation du crédit les plus importantes du pays, nous avons examiné le recours aux cartes de crédit et aux marges de crédit hypothécaires des Canadiens. Sur les figures illustrant la distribution des soldes impayés de cartes de crédit et de marges de crédit hypothécaires, nous constatons un important déplacement vers la gauche, ce qui reflète un fléchissement généralisé du recours au crédit. Nos résultats suggèrent qu'au cours de la récession provoquée par la COVID‐19, les consommateurs canadiens ont pu satisfaire leurs besoins financiers sans alourdir leurs dettes. Ces conclusions complètent d'autres observations, notamment sur la baisse des dépenses de consommation ou sur l'effet des programmes d'aide du gouvernement, et laissent entendre que les conséquences économiques de cette pandémie sont très différentes de celles observées dans d'autres types de récession.